Making sparse distance measurements feasible in robotic localization with rotating ultra-wideband tag - Liu, Jinxin (Nanyang Technological University, 2024)
The accurate localization of robots is paramount for autonomous navigation and effective operation in collaborative multi-robot systems. Among various sensing technologies, Ultra-Wideband (UWB) distinguishes itself due to its good localization accuracy, robustness against environmental interferences, and the unique ability to provide localization with ID information at a reasonable cost. Despite these advantages, traditional UWB localization often requires extensive distance measurements, posing significant challenges. This leads to a critical question: Can effective robot localization be achieved with limited distance measurements? To address this challenge, this thesis introduces an innovative concept: the rotating UWB tag. By integrating a rotating mechanical structure with UWB technology, this research demonstrates the potential for achieving accurate robotic localization using sparse distance measurements. This thesis addresses three key challenges in different UWB application contexts: minimal use of UWB tags, extensible range of localization services, and rapid deployment capability. Grounded in this concept, the thesis investigates three main domains: distributed relative localization, localization using mobile anchors, and single-anchor localization. By employing rotating UWB tags in these contexts, the study not only expands research in these areas but also establishes a cohesive logical framework for the thesis.